Computer simulations of structural and mechanical properties of cellulose allomorphs - Mashapa, Matete Gilbert (My University, 2008)
Cellulose is regarded as the most abundant polymer in nature and the first on which X-ray investigations had been performed, a year after the discovery of diffraction of X-rays on crystalline materials in 1912. It is one of the most abundant and important polymers on the planet. It comprises of four allomorphs, cellulose Iβ, II, III and IV1 and IV2 of which Iβ and II are the most stable and industrially important. Cellulose I is the native form of cellulose. Molecular dynamics (MD) simulations have been carried out to study the structural and mechanical properties of cellulose, cellulose Iβ, II, III and IV1 and IV2 bulk systems. Simulations were carried out using Polymer Consistence Force Field (PCFF) and Compass force field in conjunction with the Discover simulation program at various temperatures. We used molecular dynamics simulation to obtain a better insight about temperature dependence of cellulose. Further investigations on mechanical properties of this material at various temperatures were carried out. Using pair correlation functions g(r) or radial distribution functions (rdf’s) we were able to investigate phase transitions wherein as the temperature was increased we observed peak broadening. These enabled us to study the similarities between the structures investigated. Also studied was water uptake in celluloses by way of introducing water at different concentrations. Analysis of lattice parameters compared reasonably well with the experimental. Lattice parameters were calculated using PCFF and they compared well with results found using Compass force field. Calculation of temperature and pressure dependence on bulk systems has been done and it was noted that as the pressure increases the lattice parameters decrease.
Thesis (M.Sc. (Agriculture)) --University of Limpopo,2008
Keywords: Computer simulations; Cellulose structural properties; Cellolose mechanical properties; Cellulose allomorphs; 661.802482; Cellulose; Biotechnology